ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA MINAT MAHASISWA MENJADI NASABAH BANK MINI SYARIAH (STUDI KASUS BANK MINI SYARIAH UINSA) - Siti Izzatul Bariyah (JSE: Jurnal Sharia Economica, 2023)
The background of this research is because there are many Islamic campuses, especially Uinsa campus students, who lack an understanding of Islamic sciences, especially knowledge, service, promotion in Islamic banking. The purpose of this study is to analyze the factors that influence the low interest of students to become customers of the Uinsa Syariah Mini Bank. The population used in this study were Uinsa students and female students with a total of 50 respondents. In conducting research the authors used two methods, namely quantitative methods and descriptive methods. In the quantitative method the authors use multiple linear regression formula. Meanwhile, in the descriptive method the author made direct observations at the research location. Regarding the results of research conducted by the authors, the factors of knowledge, service, promotion, location are factors that influence students' interest in becoming customers to become Uinsa's mini sharia bank. This statement is explained regarding the results of the questionnaire that the author uses and the results of the calculations that the author performs. Related to this, Bank Mini Syariah must have efforts that include increasing promotional and marketing activities and providing education related to BMS among students, as well as improving quality in the field of service.